Here comes the sun [large type] : a novel - Dennis-Benn, Nicole (Thorndike Press, 2016)
At an opulent resort in Montego Bay, Margot hustles to send her younger sister, Thandi, to school. Taught as a girl to trade her sexuality for survival, Margot is ruthlessly determined to shield Thandi from the same fate. When plans for a new hotel threaten their village, Margot sees not only an opportunity for her own financial independence but also perhaps a chance to admit a shocking secret: her forbidden love for another woman. As they face the impending destruction of their community, each woman fighting to balance the burdens she shoulders with the freedom she craves must confront long-hidden scars.